THE IMPLEMENTATION OF GIVING ENGLISH SUBTITLE IN A MOVIE TO IMPROVE STUDENTS LISTENING ABILITY - Helta Anggia; Yulia Gusmiarni; Yanuarius Yanu Dharmawan (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
The aim of this study is the implementation of giving English Subtitle in a movie to improve students’ listening ability. It is to look at the process of implementing the use of movies in learning listening through English movie and giving subtitles using the movie maker application. This research consisted of two instruments, observation and interview. This research focused on planning, identifying, implementing, and evaluating the improvement of students’ listening comprehension ability. The study uses qualitative method. It is exploring and understanding the meaning of individuals or groups. To improve the students listening comprehension ability, we focused on using English subtitle in a movie. After the students added the subtitles in a movie, they felt challenged and they could understand the listening text as well as the knowledge that they had never known before.